Socialization of the Role of Paralegals in Meeting Legal Aid and Sustainable Development Goals (SDGs) in the field of Education - I Wayan Parsa; Ayu Putu Laksmi Danyathi; I Gusti Ngurah Nangga Jaya Dininggrat; I Gede Janitra Rad Winatha; Thomas John Kenevan (Focus Journal : Law Review, 2025)
The socialization related to the role of paralegals in fulfilling legal assistance is very important to be applied, especially in rural areas, so that the community in the village can know and understand the role of paralegals in fulfilling legal assistance, and subsequently, the community in the village can access legal assistance from paralegals. In addition, the importance of socialization regarding the Sustainable Development Goals (SDGs) in the field of Education is that it will provide knowledge to the community in the village about the access to education that can be obtained. The research method used in this study is a research method that utilizes references from books and journals related to the socialization regarding the role of paralegals in fulfilling legal assistance and the socialization about the Sustainable Development Goals (SDGs) in the field of Education. The research findings indicate that the issues faced by the community in the village regarding access to Paralegals in fulfilling Legal Aid include the need for socialization of regulations related to the Role of Paralegals in fulfilling Legal Aid as stipulated in Law No. 16 of 2011 on Legal Aid & Regulation of the Minister of Law and Human Rights No. 3 of 2021 on Paralegals in Providing Legal Aid. Furthermore, the Sustainable Development Goals (SDGs) in the field of Education is quality education, aimed at ensuring equitable distribution of quality education and increasing learning opportunities for all. Thus, with knowledge and higher education, individuals will directly understand the regulations related to access to legal aid.